The Effect of Counseling about Vulva Hygiene During Menstruation on the Level of Knowledge of Adolescent - Dewi Rakhmawati; Khoirul Anam (Universitas Islam Jember, 2022)
Poor young women's knowledge about vulva hygiene during menstruation can be one of the originators of various complaints and problems related to reproductive health. Vulva hygiene that is not done properly can cause infections in the vaginal area that can increase the risk of malignancy such as cervical cancer. The purpose of this study was to determine the effect of counseling about vulva hygiene during menstruation on the level of knowledge of young women at MTS Miftahul Ulum Silo Jember. The research design used was pre-experimental with a one-group pretest-posttest design. The population in this study was young women at MTS Miftahul Ulum Silo Jember with a random sampling technique obtained by 40 people. Instrumen research questionnaire. Analysis using wilcoxon signed ranks. The results showed a p-value of 0.000 (< α = 0.05) meaning that there was an influence of counseling about vulva hygiene during menstruation on the level of knowledge of young women at MTS Miftahul Ulum Silo Jember.